Compensatory effects of different exercise durations on non-exercise physical activity, appetite, and energy intake in normal weight and overweight adults - Liu, Xiao-Mei; Wang, Ke; Zhu, Zheng; Cao, Zhen-Bo (Frontiers in Physiology, 2022)
Objectives: To examine compensatory changes of different exercise durations on non-exercise physical activity (NEPA), appetite, and energy intake (EI) in normal and overweight adults, and to determine if different body mass index of individuals interact with these compensatory effects. Methods: Ten normal weight adults (nine females and one male; age: 24.0 ± 0.4 years; BMI: 20.7 ± 0.5 kg/m2) and ten overweight adults (six females and four males; age: 24.5 ± 0.9 years; BMI: 25.9 ± 0.4 kg/m2) participated in this study. The participants completed two exercise trials: short-duration continuous training (SDCT) and long-duration continuous training (LDCT), i.e., a 40 min short-duration and an 80 min long-duration continuous training in a randomized order. Total physical activity and NEPA were monitored using an accelerometer for seven consecutive days, which involved a two-day baseline observation period (C-pre-Ex), three-day exercise intervention period (Ex), and two-day follow-up period (C-post-Ex). Blood samples were collected for appetite-related hormone analysis. Appetite score was assessed using the visual analogue scale. Energy intake was evaluated by weighing the food and recording diaries. Results: The NEPA evaluation showed that it was higher for SDCT than for LDCT in the C-post-Ex period (F (1, 19) = 8.508, p = 0.009) in the total sample. Moreover, results also indicated that NEPA was lower for LDCT (F (2, 18) = 6.316, p = 0.020) and higher for SDCT (F (2, 18) = 3.889, p = 0.026) in the C-post-Ex period than in the C-pre-Ex and Ex periods in overweight group. Acyl-ghrelin revealed a main effect of time in the total sample and in normal weight and overweight groups; it was lower in the C-post-Ex period than in the C-pre-Ex and Ex periods (all p < 0.05). Total EI analysis revealed no significant changes in either the total sample or in the normal weight and overweight groups. Conclusion: These findings demonstrate that short duration exercise led to a compensatory increment in NEPA, whereas long duration exercise induced a compensatory decrease in NEPA. Moreover, there was a higher and delayed compensatory response in overweight adults than in normal weight adults. Nevertheless, energy intake was not changed across time, regardless of exercise duration.